Basic English grammar - Woods, Geraldine (--For dummies., 2024)
Basic English Grammar For Dummies is the bestselling grammar guide that's perfect for readers who want to improve their knowledge of the English language. This well-rounded primer covers the building blocks of English grammar, giving you an introduction to parts of speech, sentence structure, punctuation, capitalization, and more. Real-world examples help you understand the rules of Standard English and when you can break them! You can test your progress with quiz questions on every topic. This updated edition explains current usage (including pronouns and presentation slides) and gives you handy rules to remember, so you can speak and write with confidence. Make the English language learning process engaging and stress-free with this Dummies guide. Learn about parts of speech, sentence structure, punctuation, and capitalization ; Become a better writer and get answers to all your questions about English ; Recognize and avoid common grammar mistakes and misuse of words ; Apply your grammar knowledge in everyday scenarios at work, in school, and in general communication Anyone who's new to the English language or needs a little refresher on tricky grammar rules will enjoy Basic English Grammar For Dummies. This book makes learning the English language accessible so you can feel confident at work, in school, and in life.